1998
DOI: 10.1177/0002764298041008007
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Need for Health Care and Use of Health Care by Injection-Drug Users, Other Chronic Drug Users, and Nondrug Users

Abstract: This article compares the health care need and health care use of injection drug users, other chronic drug users, and nondrug users. Data from 1,330 non-Hispanic White, African American, and Hispanic/Latino men and women were analyzed to determine independent risk factors for two outcome variables: (a) need for health care treatment and (b) use of health care treatment. Ten independent demographic, health, and drug use variables were assessed in logistic regression models. Drug use (injection drug use or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 30 publications
6
48
0
Order By: Relevance
“…Chronic users in their study were significantly less likely than nonusers to receive services, despite an increased need for health care. Being female was also independently associated with an increased need for care in their sample, 17 further highlighting the importance of the drug-using women in our sample not receiving needed care. Results of this study corroborate their reported findings, but we also contrasted separately three frequency categories of users with nonusers.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Chronic users in their study were significantly less likely than nonusers to receive services, despite an increased need for health care. Being female was also independently associated with an increased need for care in their sample, 17 further highlighting the importance of the drug-using women in our sample not receiving needed care. Results of this study corroborate their reported findings, but we also contrasted separately three frequency categories of users with nonusers.…”
Section: Discussionmentioning
confidence: 67%
“…For example, users and nonusers in our sample differed in the likelihood of failing to seek needed care only when the complete drug use history was considered (data not shown). Chitwood and colleagues 17 have demonstrated the lack of health service treatment among chronic (e.g., using illegal drugs weekly or more 37 ) drug users compared to nonusers. Chronic users in their study were significantly less likely than nonusers to receive services, despite an increased need for health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studying the process of health care utilization among IDUs will likely inform efforts to reduce their health problems (CDC, 2002;Chitwood et al, 1998) as well as diminish the health risks that IDUs pose to the larger community and ease the strain on emergency and follow-up care systems (CDC, 2002;French, McGeary, Chitwood, & McCoy, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that those who use illicit drugs are medically underserved (Chitwood et al, 1998;Wood et al, 2004). Active drug users, even in a setting providing free HAART, experience difficulty obtaining care for HIV-related illnesses (Cunningham et al, 1995;Strathdee et al, 1998).…”
Section: Stigma and Discrimination In A Health Care Facilitymentioning
confidence: 99%